A New Chromone from the Stems of Cassia fistula and Its Anti-Tobacco Mosaic Virus Activity - Deng, Liang; Li, Lan; Xu, Wenxiu; Hu, Qiufen; Gao, Xuemei; Guo, Yadong (Asian Journal of Chemistry, 2014)
A new chromone 8-methoxy-2,2-dimethyl-7-(2-oxopropyl)-2,3-dihydrochromen-4-one (1) was isolated from the stems of Cassia fistula. Its structures was elucidated by spectroscopic methods, including extensive 1D- and 2D NMR techniques. Compound 1 was evaluated for its anti-tobacco mosaic virus (anti-TMV) activity. The results showed that compound 1 exhibit potential anti-TMV activity with inhibition rates of 23.5 %.